Dorsal column pathway is involved in tactile reward-induced affective 50-kHz ultrasonic vocalizations in rats - Rie Shimoju (PLoS ONE, 2025)
Rhythmic stroking induces positive emotions in rats via the mesolimbic dopamine system. However, the ascending pathways underlying the affective 50-kHz ultrasonic vocalizations (USVs) induced by somatosensory stimulation remain unknown. The dorsal column consists of ascending spinal tracts that convey innocuous tactile information from the spinal cord to the brain. Here, we investigated whether the somatosensory signals transmitted through the dorsal column pathway contribute to the induction of positive 50-kHz USVs during rhythmic stroking. The 50-kHz USVs, behavior, approach latency, and mechanical tactile thresholds of animals with dorsal column lesions (DCL) at the upper thoracic level were compared with those in sham-operated animals. The DCL significantly reduced the number of 50-kHz USVs, harmonics, and split calls during rhythmic stroking, and the number of hedonic frequency-modulated calls (trill, complex, and step up calls) after rhythmic stroking. The DCL significantly increased the approach latency compared to presurgical controls. Sham-operated rats demonstrated a significant increase in the number of 50-kHz USVs and shortened approach latency compared with presurgical control values. Our results suggest that the somatosensory input conveyed by the dorsal column triggers the affective 50-kHz USVs during rhythmic stroking and approach behaviors. These findings contribute to revealing the neural circuits underlying somatosensory-emotional integration.